Unilateral erythema nodosum in a 17-year-old girl. - Ventura Lourenco, J.; Mazeda, I.; Oliveira, J.; Martins, A.; Ramos, S. (European Journal of Pediatric Dermatology, 2025)
Erythema nodosum, the most prevalent form of panniculitis, usually affects women in their 3rd and 4th decades of life, presenting as tender, erythematous nodules on the legs. It arises from delayed hypersensitivity reactions, often triggered by various factors, including infections, especially those caused by Streptococcus. Unilateral erythema nodosum in pediatric patients is exceedingly rare, with only one previously documented case. We present the case of a 17-year-old girl that initially presented with a painful, erythematous induration of her left leg, mimicking cellulitis. Despite initial treatment with antibiotics, further evaluation revealed elevated antistreptolysin O titres and imaging findings consistent with erythema nodosum. Dermatological consultation confirmed the diagnosis, and the lesions resolved within 8 weeks. This case underscores the importance of a thorough evaluation and consideration of atypical presentations in diagnosing erythema nodosum, particularly in pediatric patients. A comprehensive approach to patient care is essential to ensure accurate diagnosis and appropriate management.